Tata Kelola Manajemen Risiko Pada PT Unilever Indonesia, Tbk - Ratnawaty Marginingsih (Universitas Bina Sarana Informatika, 2017)
Abstract— Risk management is an important part of management strategies all companies. The process whereby an organization appropriate the method is able to show risks happened one activity leading to success in in each of activity of all activities. The focus of risk management is identification and means of overcoming a risk. The targets to add value to maximum sustainable the organization. The role of risk management is expected to anticipate environment rapidly changing,, develop corporate governance, optimize strategic management, secure the sources of resources and asset owned organization and reduce reactive decision making from management the top. Risk management activities includes all the act of to give rest from the operations of a firm and supply rest soul required by all personnel company (including the owner, chairman and employees of a company) .Research methodology used for writing it is a technique descriptive analysis qualitative. Technique data collection used the literature study .Object research were management and the application of on risk management PT Unilever Indonesia, Tbk a period of the year 2015-2016 .Keywords: Governance, Risk Management